The Role of Satisfaction in Mediating the Association of Pesantren Brand Image and Price Fairness on Customer Loyalty in Pesantren Cooperatives - Muhammad Alaudin; Abu Yasid; Iskandar Ritonga (CV. Sakura Digital Nusantara, 2026)
Purpose – This study examines the association between pesantren brand image and price fairness with customer loyalty in pesantren cooperatives in East Java, with customer satisfaction as a mediating variable. This study is important because pesantren cooperatives operate not only as business institutions, but also as institutions representing religious and social values that may be associated with customer loyalty. Design/methodology/approach – This study employed a quantitative method using a cross-sectional approach. Data were collected through online questionnaires distributed to consumers who had experience purchasing products at pesantren cooperatives in East Java. A total of 209 respondents participated in this study, and the data were analysed using SEM-PLS to examine the relationships among variables. Finding/Results – The results indicate that pesantren brand image is positively and significantly associated with customer loyalty (β = 0.213) and customer satisfaction (β = 0.323). Price fairness is similarly positively and significantly associated with customer loyalty (β = 0.208) and customer satisfaction (β = 0.279). Customer satisfaction is the strongest direct predictor of customer loyalty (β = 0.411). Mediation analysis reveals that customer satisfaction partially mediates the relationship between pesantren brand image and customer loyalty (β = 0.067) and the relationship between price fairness and customer loyalty (β = 0.166), with the latter demonstrating a substantially stronger mediating role. Research Implications/Limitations – The findings provide additional insights into the application of satisfaction-mediated loyalty models within faith-based cooperative settings. However, the cross-sectional design limits the causal interpretation of the observed relationships. In addition, the focus on pesantren cooperatives in East Java limits the broader generalizability of the findings. Originality/Value – This study extends customer loyalty research within the context of pesantren cooperatives and highlights the importance of religious institutional image and fair pricing in their positive association with customer satisfaction and loyalty.